The Development of Electricity Board Learning Media with Running Light System Starter for Learning in Vocational High School - Aris Sulistiyanto; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Jurnal E-Komtek, 2022)
The students of grade XI of the Motorcycle Business Engineering of Vocational High School, who have learned productive subject matter in Motorcycle Engineering and Business, often experience difficulties when directly confronted with motorcycle practice media because the components are closed and hidden by the motorcycle's body cover. Therefore, a learning media which is easy to be learned by the students is essential. It means that all components can be observed clearly, and the material can be understood easily, both in theory and electrical practicum of the motorcycle starter system; the students will better understand the theory and assemble the motorcycle starter system circuit. The learning media for the motorcycle starter system is an electrical board with LEDs that can light up continuously or alternately, so it simulate the workings of the motorcycle starter system. In addition, the running LED simulation makes it easier for students to assemble a starter system. It also makes it easy and fast for students to identify, understand how it works, assemble a motorcycle starter system, and later, when facing practical materials in the form of motorbikes, students will be quicker to apply the material that they acquired from the learning media, so that, in practicum, students will work faster and minimize damage to motorcycles.